2019
DOI: 10.1002/jcph.1493
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Ontogeny of Hepatic UDP‐Glucuronosyltransferase Enzymes Based on Glucuronidation Activity Measured in Human Liver Microsomes

Abstract: An understanding of the postnatal development of hepatic UDP‐glucuronosyltransferase (UGT) enzymes is required for accurate prediction of the age‐dependent changes in pharmacokinetics of many drugs used in children. However, the maturation rate of hepatic UGT isoforms remains a major knowledge gap. This study aimed to establish the age‐associated changes in glucuronidation activity of 10 major hepatic UGT isoforms in humans, namely, UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A9, UGT2B4, UGT2B7, UGT2B10, UGT2B15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…In agreement with previous literature, UGT1A4, UGT1A6, and UGT2B17 activities were found to increase from infant age to adulthood 3 . UGT2B17 increased slowly, with adult levels reached at adolescence.…”
Section: Updates On Ontogeny Information Involved In Drug Dispositionsupporting
confidence: 92%
“…In agreement with previous literature, UGT1A4, UGT1A6, and UGT2B17 activities were found to increase from infant age to adulthood 3 . UGT2B17 increased slowly, with adult levels reached at adolescence.…”
Section: Updates On Ontogeny Information Involved In Drug Dispositionsupporting
confidence: 92%
“…These children showed a higher inter-individual variability on CL/F compared to that of adults (63.0% vs. 24.2% or 37.9%) [40,41]. This might be partly attributable to the age-associated maturation of hepatic UGT1A4 [135].…”
Section: Pediatricsmentioning
confidence: 99%
“…Studies focusing on individual isoforms have shown that the glucuronidation activities of human hepatic isoforms develop in an age‐dependent manner, and protein expression may not correlate with activity . The protein expression–enzyme activity disconnect demonstrated within the UGT enzymes during development, which has been comprehensively discussed, presents a challenge for accurately predicting drug biotransformation and, therefore, drug response in children. UGT proteins may be present in truncated or partially active forms.…”
Section: Discussionmentioning
confidence: 99%
“…This method could therefore complement proteomics approaches in which the protein is proteolytically degraded before quantitation of defined peptide fragments. We cannot, however, rule out the possibility that full‐length but inactive protein could be quantified using the blotting method; these inactive UGT proteins have generally been shown to exist in fetal and neonatal livers with activity being mature within approximately 24 months of life . In terms of practical applications for dose selection, these data imply that the allometric approach (down to 2 years of age) will give different data from a physiologically based pharmacokinetic approach and may be less accurate due to reliance on intrinsic clearances.…”
Section: Discussionmentioning
confidence: 99%